2005
DOI: 10.1007/s00705-005-0554-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a tobacco protein interacting with tomato mosaic virus coat protein and facilitating long-distance movement of virus

Abstract: The protein-protein interaction of virus and host is essential for virus infection and host defense. The coat protein (CP) of tomato mosaic virus (ToMV) has been proved to be involved in cell-to-cell and long-distance movements of viruses that are presumably related with the protein-protein interactions. However, the host proteins that interact with the ToMV coat protein (ToCP) are largely unknown. In this study, we isolated a cDNA from a tobacco library through yeast two-hybrid system, which encodes a protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Viral systemic symptom development can be used as an indicator to monitor long-distance trafficking of ToMV and other plant viruses (Leisner et al, 1993;Li et al, 2005;Lewis and Lazarowitz, 2010). In N. benthamiana, ToMV systemic infection resulted in curved apical shoots, crinkled apical leaves, chlorotic mottling of newly emerged leaves, and backward winding of young leaves (Fig.…”
Section: Silencing Of Nbrbcs Enables Tomv To Induce Local Necrosis Bumentioning
confidence: 99%
“…Viral systemic symptom development can be used as an indicator to monitor long-distance trafficking of ToMV and other plant viruses (Leisner et al, 1993;Li et al, 2005;Lewis and Lazarowitz, 2010). In N. benthamiana, ToMV systemic infection resulted in curved apical shoots, crinkled apical leaves, chlorotic mottling of newly emerged leaves, and backward winding of young leaves (Fig.…”
Section: Silencing Of Nbrbcs Enables Tomv To Induce Local Necrosis Bumentioning
confidence: 99%
“…A putative oxidoreductase, HCP1, interacts with the brome mosaic virus (BMV) CP and affects BMV infection in barley (Okinaka et al, 2003). It has also been reported that high expression of a tomato mosaic virus CP-interacting protein is necessary to assist virus long-distance movement (Li et al, 2005). However, none of these studies has linked CP to its interactions with host proteins in peroxisomes, which play an essential role in specific defence mechanisms conferring resistance against pathogens and also have important functions in metabolism (Koh et al, 2005;Lipka et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, part of the TMV CP population localizes inside chloroplasts, where it is thought to induce chlorosis by interfering with PSII functions Beachy, 1986, 1989;Hodgson et al, 1989;Culver, 2002;Lehto et al, 2003). Likewise, a fraction of the ToMV CP has also been reported to localize inside chloroplasts, where it is thought to interact with a thylakoid membrane protein (Li et al, 2005;Zhang et al, 2008).…”
Section: Is Thf1 Involved In Effector Recognition or Downstream Signamentioning
confidence: 99%